Pengaruh Social Commerce Instagram dan Celebrity Endorser terhadap Minat Beli Moisturizer pada Mahasiswi Program Studi Tata Rias dan Kecantikan FPP UNP - Rahmawati Aulia; Tyas Asih Surya Mentari (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated because self-confidence in using skincare products recommended by celebrity endorsers is also an important factor in purchasing decisions. The purpose of this study was to analyze the influence of celebrity endorser Tasya Farasya and Instagram social commerce on the purchase decision of the Originote skincare moisturizer on female students of the FPP UNP Makeup and Beauty Education Study Program. This type of research is Ex post Facto with a quantitative research method approach. The population of this study were female students of the 2020, 2021, 2022 and 2023 Makeup and Beauty Education Study Program, namely 365 people. The type of sampling used in this study was non-probability with a purposive sampling technique with a total of 78 people. Data were collected through observation methods and research questionnaires. The preparation of the instrument was carried out by sorting the Likert scale. Data were analyzed by descriptive analysis, normality tests and hypothesis tests. The results of the study obtained 1) Instagram social commerce partially has a significant effect on Moisturizer Purchase Interest in Female Students of the FPP UNP Makeup and Beauty Study Program. 2) Celebrity endorser Tasya Farasya partially has a significant effect on the Moisturizer Purchase Interest of Female Students of the Makeup and Beauty Study Program, FPP UNP. 3) Celebrity Endorser Tasya Farasya and Social Commerce Instagram simultaneously influence the purchase decision of the Originote skincare moisturizer for female students of the Makeup and Beauty Education Study Program, FPP UNP. Suggestions to increase insight into the material in the lesson for students, in increasing knowledge and information about the influence of celebrity endorser Tasya Farasya Instagram social media on the purchase decision of the Originote skincare moisturizer for female students of the Makeup and Beauty Education Study Program, FPP UNP.